1989
DOI: 10.1161/01.hyp.13.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril prevents stroke and kidney dysfunction in salt-loaded stroke-prone spontaneously hypertensive rats.

Abstract: The influence of chronic treatment with the angiotensin I converting enzyme (ACE) inhibitor enalapril on blood pressure, kidney function, and survival was examined in stroke-prone spontaneously hypertensive rats (SHRSP). Male SHRSP that were fed a Japanese rat chow plus a 1% NaCl drinking solution beginning at 7-8 weeks of age developed severe hypertension and stroke; 14 of 18 untreated control SHRSP died by 14 weeks of age and exhibited evidence of cerebrovascular lesions. When enalapril (15 mg/kg/day) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 40 publications
(28 reference statements)
6
67
1
Order By: Relevance
“…However, in spite of the lack of effect on these cardiovascular variables, ramipril protected against stroke and mortality. In agreement with our observation, Stier et al (1989) also found that, during a high intake of sodium chloride, ACEI treatment decreased SHRSP mortality. The mechanism of this protective effect of ACEI is not clear.…”
Section: Plasma Electrolytes and Renin Activitysupporting
confidence: 93%
“…However, in spite of the lack of effect on these cardiovascular variables, ramipril protected against stroke and mortality. In agreement with our observation, Stier et al (1989) also found that, during a high intake of sodium chloride, ACEI treatment decreased SHRSP mortality. The mechanism of this protective effect of ACEI is not clear.…”
Section: Plasma Electrolytes and Renin Activitysupporting
confidence: 93%
“…Enalapril, another ACE inhibitor, reduces stroke in SHRSP that are fed a high salt diet. 45 In this study, stroke was prevented by both cilazapril and hydralazine, even though hydralazine was less effective than cilazapril in reducing mean arterial pressure. Thus, our data suggest that even moderate reductions in mean arterial pressure are effective in preventing stroke in SHRSP.…”
Section: Strokementioning
confidence: 60%
“…Similar improvement in animal survival independent of blood pressure effects has been demonstrated in a group of nondiabetic, salt-loaded, stroke-prone SHR treated with enalapril. 17 Other studies have shown that treatment with ACE inhibitors reduces blood pressure and prolongs life in experimental models of renal failure. 1315 Long-term intracerebral treatment with captopril can reduce the salt appetite in SHR.…”
Section: Discussionmentioning
confidence: 99%